QUALITY IMPROVEMENT ANALYSIS USING THE SEVEN NEW QUALITY TOOLS AND POKA YOKE IN A SAFETY SHOES MANUFACTURING COMPANY - Nathaniel; Wilson Kosasih; Lithrone Laricha Salomon (Universitas Tarumanagara, 2025)
This safety shoe company is a manufacturing company that faces various quality issues, such as defects in stitching, leather, mismatched shoe pairs, and incomplete components. Based on production data from March 2024 to February 2025, the most dominant defects were “Mismatched Pairs” and “Incomplete Components,” with a total of 3,694 defective pairs out of 120,000 produced, resulting in a DPMO value of 7,695.83. This study aims to identify the root causes of these defects and design quality improvement solutions using the New Seven Quality Tools and PokaYoke methods. Data were collected through field observations and literature reviews, then analyzed using tools such as the Pareto Diagram, Affinity Diagram, Interrelationship Diagram, Tree Diagram, and Matrix Analysis. The results show that immediate corrective actions include the development of standard operating procedures (SOPs), routine socialization, daily briefings, improved lighting, and component replacement. Long- term solutions, such as adding conveyor belts and implementing preventive maintenance, could not yet be executed due to time and cost constraints. Implementation efforts focused on developing a Poka Yoke-based SOP at the packing station as a concrete step toward improving product quality.